A JWST Study of the Remarkable Oort Cloud Comet C/2017 K2 (PanSTARRS) - Charles E. Woodward; Dominique Bockélee-Morvan; David E. Harker; Michael S. P. Kelley; Nathan X. Roth; Diane H. Wooden; Stefanie N. Milam (The Planetary Science Journal)
Comets, during their journeys into the inner solar system, deliver volatile gases, organics, and particulates into their comae that provide crucial information for assessing the physicochemical conditions in the outer disk from which they formed. Here we present observational and modeling results of a JWST NIRSpec and MIRI MRS integral field unit spatial-spectral study of the inner coma of the Oort Cloud comet C/2017 K2 (PanSTARRS) at a heliocentric distance of 2.35 au. We find that the comet is hyperactive (water-ice active fraction ≳86%), with a nucleus radius of <4.2 km, exhibiting strong emission from H _2 O, ^12 CO, ^13 CO, and CO _2 , as well as CN, H _2 CO, CH _3 OH, CH _4 , C _2 H _6 , HCN, NH _2 , and OH prompt emission. The water ortho-to-para ratio is ≳2.75.  The modeled dust composition (relative mass fraction of the submicron grains) in the coma is dominated by amorphous carbon (≃25%), amorphous Mg:Fe olivine (≃19%), amorphous Mg:Fe pyroxene (≃16%), and Mg-rich crystalline olivine (≃39%), and the crystalline mass fraction of the submicron grains in the coma is f _cryst  ≃ 0.384 ± 0.065. Analysis of residuals in the 3–8 μ m region of the spectral energy distribution strongly suggests the presence of polycyclic aromatic hydrocarbon species in the coma.